Adaptive Fuzzy Type-2 Synergetic Control Based on Bat Optimization for Multi-Machine Power System Stabilizers - Nechadi, E. (Engineering, Technology & Applied Science Research, 2019)
A new, adaptive, fuzzy type-2 fast terminal, synergetic multi-machine power system stabilizer is proposed in this study, based on the Bat algorithm. The time spent to reach the equilibrium point, from any initial state, is guaranteed to be finite. The adaptive fuzzy type-2 design is applied to estimate the unknown functions of a multi-machine power system. The parameters of the fast terminal synergetic control are optimized, using bat metaheuristic method. In order to test the robustness of the proposed stabilizer, three load conditions, of the multi-machine power system are studied. A comparison of the proposed adaptive fuzzy type-2 synergetic power system stabilizer with bat conventional approach is presented, indicating improved performance. The control system stability is assessed by the second theorem of Lyapunov and is proven to be asymptotically stable.